Dynamics of language systems in the era of digitalization - Larysa Kravets; Лариса Кравець; Kravec Larissza; Natalie Venzhynovych; Bolin Zhang; Ivan Poliuzhyn; Renata Lukanynets (Cises srl, 2025)
Abstract. The relevance of this article determines the need to study the changes occurring in the Ukrainian language under the influence of digital technologies. The aim of the article is to determine the extent of changes in the Ukrainian language caused by the development of digital technologies. To achieve this goal, a substantial body of scholarly works on the subject was reviewed, the empirical data sources were identified, and linguistic units were collected and analyzed. The study employs a set of theoretical research methods, including Computer-Mediated Discourse Analysis. It was found that the most significant changes occur in the language of computer-mediated communication, particularly in social media, and these changes influence other spheres of human interaction as well as the norms of standard literary language. The most noticeable dynamics were recorded in several linguistic subsystems: lexical, syntactic, and stylistic systems. The specific features of computer-mediated communication also manifest in the disregard of standard Ukrainian orthographic norms, such as the use of capital letters, and in punctuation, as evidenced by the minimization of punctuation marks. The study demonstrates that digital technologies intensify the development of the Ukrainian language by activating processes in various subsystems and expanding the domains of its functioning.
Keywords: Language system; Language norm; Dynamics of the language system; Social media; Computer-mediated communication